PENERAPAN PENDIDIKAN KARAKTER BERBASIS DIGITAL PADA MATA PELAJARAN IPS SISWA KELAS V UPT SD NEGERI 75 BENTANG - Nur Asni; Khaliq Aulia Alimin; Fitri Yanti Muchtar (STKIP Subang, 2026)
This study aims to describe the implementation of character education through digital-based Social Studies (IPS) learning and its impact on the creativity and independence of fifth-grade students at UPT SD Negeri 75 Bentang. The background of this research arises from the limited use of digital media in Social Studies learning, which results in insufficient development of students’ character, creativity, and independence. The study employed a qualitative descriptive approach, with the participants consisting of 24 students and one Social Studies teacher. Data were collected through observation, interviews, and documentation, then analyzed descriptively to illustrate the learning process and its outcomes. The results show that the use of digital media such as Canva and motivational videos on character education effectively increased students’ interest, participation, and understanding of character values such as religiosity, nationalism, independence, cooperation, and integrity. Digital-based learning also encouraged students to think creatively, express their opinions confidently, and learn independently without relying too much on the teacher.